Reframing MSME Sustainability through Contextualized Islamic Law and Local Wisdom: Financial Knowledge, Risk-Taking, and Dynamic Capability Perspective - Yuli Agustina; Sumiati Sumiati; Siti Aisjah; Risna Wijayanti (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2026)
Eco-friendly small and medium enterprises (SMEs) increasingly face sustainability challenges driven by financial uncertainty, competitive pressure, and environmental responsibility. This study examines how financial knowledge, financial skills, and financial risk-taking influence SME sustainability, while testing the mediating role of dynamic capability and the moderating role of local wisdom. Grounded in the dynamic capability framework, this research argues that financial competence alone is insufficient unless entrepreneurs can transform resources into adaptive and innovative capabilities. A quantitative approach was employed using survey data collected from eco-friendly SME owners across East Java Province, Indonesia. The proposed moderated mediation model was analyzed using Structural Equation Modeling (SEM). The results demonstrate that financial knowledge, financial skills, and risk-taking behavior significantly enhance SME sustainability. Moreover, dynamic capability partially mediates these relationships, indicating that financial competence contributes to sustainability primarily through the ability to sense opportunities, seize strategic actions, and reconfigure resources in response to market and environmental changes. The moderation analysis further reveals that local wisdom strengthens the relationship between financial competence and dynamic capability, as well as its subsequent effect on sustainability. These findings highlight that culturally embedded values and community-based practices enhance entrepreneurial resilience and support sustainable decision-making. This study contributes theoretically by integrating financial behavioral factors, dynamic capability theory, and local cultural context into a unified sustainability model for SMEs. From the perspective of Contextualized Islamic Law, these findings resonate with the principles of maqāṣid al-sharīʿah, particularly the preservation of wealth (ḥifẓ al-māl), public welfare (maṣlaḥah ʿāmmah), social cooperation (taʿāwun), and environmental protection (ḥifẓ al-biʿah), which collectively provide a normative foundation for sustainable entrepreneurship. Accordingly, the sustainability of eco-friendly SMEs may be understood not only as an economic objective but also as the realization of Islamic ethical values through the integration of financial competence, adaptive capability, and local wisdom. Practically, the study suggests that SME development programs should emphasize not only financial education but also capability-building interventions aligned with local wisdom to strengthen long-term sustainability in green-oriented enterprises